Requirements for sustainable operation and maintenance of rural small-scale water infrastructure in Limpopo Province, South Africa - Selala, MS; Senzanje, A; Dhavu, K (Water SA, 2019)
This study assessed the presence of key requirements for sustainable O&M and rehabilitation of rural small-scale water infrastructure in Makhudutamaga Municipality in South Africa. The study found a significant correlation between the requirements for sustainable O&M and rehabilitation of rural small-scale water infrastructure and continuity of service provision (p < 0.001) by the small-scale water infrastructure as well as functionality (p < 0.001) of the small-scale water infrastructure hardware. The study concludes that the presence of the key requirements varies as a function of social dynamics of communities and the presence of these requirements has an impact on the functionality and continuity of the small-scale water infrastructure hardware.